Sasirangan Motif Modification Training for the People of North Loktabat to Foster An Entrepreneurial Spirit - Gusti Marliani; Surti Surti (Universitas Brawijaya, 2021)
This Community Service aims to provide knowledge about making Sasirangan cloth with various motifs that can increase competitiveness in the market because different and rare motifs are found. The service method used is to provide direct training to the community by experts in making Sasirangan fabrics with various modifications of motifs. This training is carried out for ten days, from theoretical material to manufacturing practice until finished. Several things were concluded about the results of the movement, namely the preparation of (Kelompok Swadaya Masyarakat) KSM as an organizer was still not mature, so the sequence of activities had not been well conceptualized. Then the activities were carried out during the pandemic. Hence, it took a long time for training, which impacted the enthusiasm and commitment of participants to be disciplined in carrying out activities. Through this training, it is hoped that it will foster an entrepreneurial spirit in the North Loktabat community, especially Sasirangan artisans in this area are relatively rare. This condition is undoubtedly a good business opportunity considering that Sasirangan is a typical South Kalimantan fabric always in demand by the public, whether for daily clothing or gifts and souvenirs. In addition, the various modifications of the Sasirangan motifs make the Sasirangan look more modern and contemporary so that the competitiveness of this product increases.